2021
DOI: 10.1177/17562848211037094
|View full text |Cite
|
Sign up to set email alerts
|

Safety of anti-TNF agents in patients with compensated cirrhosis: a case-control study

Abstract: Background: There is limited data on the use of anti-TNF agents in patients with concomitant cirrhosis. The aim of this study is to assess the safety of anti-TNF agents in patients with compensated cirrhosis who used these medications for the treatment of an underlying rheumatologic condition or IBD. Methods: Multicenter, retrospective, matched, case-control study. A one to three case-control match was performed. Adults who received anti-TNF therapy were matched to three adults with cirrhosis who did not recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…There exist concerns regarding the use of anti-TNF agents in case of liver cirrhosis. In one study investigating 80 patients with compensated liver cirrhosis who received an anti-TNF agent for other reasons (240 matched controls studied), there was no evidence of increased decompensation, serious infections, malignancy, mortality, and transplant-free survival 163 . Most cases of cirrhosis in this study were because of NAFLD.…”
Section: Anti-inflammatory Therapies In Liver Diseasesmentioning
confidence: 53%
See 1 more Smart Citation
“…There exist concerns regarding the use of anti-TNF agents in case of liver cirrhosis. In one study investigating 80 patients with compensated liver cirrhosis who received an anti-TNF agent for other reasons (240 matched controls studied), there was no evidence of increased decompensation, serious infections, malignancy, mortality, and transplant-free survival 163 . Most cases of cirrhosis in this study were because of NAFLD.…”
Section: Anti-inflammatory Therapies In Liver Diseasesmentioning
confidence: 53%
“…In one study investigating 80 patients with compensated liver cirrhosis who received an anti-TNF agent for other reasons (240 matched controls studied), there was no evidence of increased decompensation, serious infections, malignancy, mortality, and transplant-free survival. [163] Most cases of cirrhosis in this study were because of NAFLD. In a large US-based retrospective cohort including 226,555 patients with immune-mediated disorders, there was no beneficial effect of any anti-TNF agent regarding development of cirrhosis, NAFLD, or NASH in such patients [164,] raising doubts that TNF neutralization might be of relevance in the treatment of NAFLD despite interesting preclinical data.…”
Section: Anti-tnf Therapiesmentioning
confidence: 75%
“…If the positive outcomes are confirmed, it could also open new possibilities to treat HE or mHE patients with liver cirrhosis given that inflammation and immune response have been suggested to play a central role in the pathogenesis of HE, as demonstrated in patients and animal models [6,8,[64][65][66]. Unfortunately, although many nonsteroidal anti-inflammatory drugs, such as ibuprofen or celecoxib, or anti-TNF-α inhibitors, including infliximab or etanercept, which have revolutionized the treatment of multiple inflammatory conditions, including rheumatoid arthritis, psoriasis and inflammatory bowel disease, have shown promising results in animal models of liver disease [6,[67][68][69][70], they have also been associated with different degrees of hepatotoxicity when tested in patients, including the reactivation of viral hepatitis, drug-induced liver injury and de novo autoimmune hepatitis [71][72][73]. Therefore, the fact that only two drugs belonging to this category have reached testing in humans indicates that more efforts are needed to reduce the enormous gap between these and the other and more classical drugs, which still dominate the pharmacological field in HE.…”
Section: Discussionmentioning
confidence: 99%
“…Although the metabolism of antibody-based medication in patients with liver cirrhosis patients has not been described in detail, it has been reported that denosumab, a human monoclonal antibody that is used for the treatment of osteoporosis, can be safely used in patients with chronic liver disease, including liver cirrhosis [24]. In addition, a fully human monoclonal anti-tumor necrosis factor-α antibody that is used for the treatment of rheumatologic conditions was shown not to increase the risks of ascites, hepatic encephalopathy, or variceal bleeding in patients with compensated cirrhosis Endocrine Journal Advance Publication [25]. Although hepatic encephalopathy occurred twice in the present patient, it also occurred prior to burosumab treatment.…”
Section: Discussionmentioning
confidence: 99%